2015
DOI: 10.1136/oemed-2014-102697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of farm modernity on the prevalence of chronic obstructive pulmonary disease in dairy farmers

Abstract: Dairy farming is associated with an excess of chronic obstructive pulmonary disease (COPD). The dairy industry has been changing for the past three decades with larger, more efficient farms and potentially less exposure to agents involved in COPD development. However, the impact of farm modernisation on COPD prevalence is unknown. We studied respiratory symptoms, respiratory function by spirometry and tobacco smoking in 575 male dairy farmers working either in traditional or in modern farms in the French Doubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…It is noteworthy that this increased risk of COPD traits among dairy farmers may have decreased during the last few years. Our group recently investigated the impact of farm modernity on respiratory outcomes such as airflow limitation and chronic bronchitis in dairy farmers 12. This study demonstrated that working in a modern farm (with a separation between the house and the cowshed and using a loose housing system) decreased the risk of airflow limitation twofold after adjustment for age and for smoking habits 12…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that this increased risk of COPD traits among dairy farmers may have decreased during the last few years. Our group recently investigated the impact of farm modernity on respiratory outcomes such as airflow limitation and chronic bronchitis in dairy farmers 12. This study demonstrated that working in a modern farm (with a separation between the house and the cowshed and using a loose housing system) decreased the risk of airflow limitation twofold after adjustment for age and for smoking habits 12…”
Section: Discussionmentioning
confidence: 99%
“…The youngest farmers are also those who are likely to be exposed for decades to occupational airborne pollutants. As it is likely that the combination of tobacco smoking and occupational exposures has an additive or even synergistic effect on COPD [ 8 ], it seems important to initiate smoking prevention strategies in active farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking is in its own right a well-established risk factor for the development of chronic respiratory diseases, especially chronic bronchitis and COPD [ 6 , 7 ]. Notably, there is an additive or even a synergistic effect on the decline in lung function and on the development of COPD [ 8 ] between tobacco and some occupational farming exposures. It therefore seems essential not only to prevent occupational exposure in farmers, but also to fight against tobacco smoking, especially in those who are exposed to noxious occupational airborne contaminants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that dairy farmers are more likely to suffer from respiratory disorders like chronic bronchitis, non-atopic asthma and chronic obstructive pulmonary disease (COPD) than is the general population (Dalphin et al, 1998;Gainet et al, 2007;Omland et al, 2011;Reynolds et al, 2013, Guillien et al, 2016. This increased risk of pulmonary disease may result from repeatedly inhaling organic dust (Eduard et al, 2009;Thaon et al, 2011;Jouneau et al, 2012;Marescaux et al, 2016).…”
Section: Introductionmentioning
confidence: 99%